The Issues of Land Tenure in Mixed Marriage - Mujiburohman, Dian Aries; Junarto, Rohmat; Salim, M Nazir; Pujiriyani, Dwi Wulan; Utami, Westi; Andari, Dwi Titik Wulan (SCAD Independent, 2023)
One of the problems in mixed marriages of different nationalities is joint property. Most mixed-married couples do not make property separation agreements because they are unaware that the Marriage Law governs them. The absence of a marriage agreement results in a mix of assets, which means that foreigners own half of the joint property. The provisions in the land law/ UUPA state that foreigners are prohibited from having land rights except for usufructuary rights and rental rights. This study applied the normative legal research method with a statutory and case-based approach. This study showed that if mixed marriage actors did not have a property separation agreement, Indonesian citizens' land rights ownership status was equal to that of the foreigners. Second, jurisprudence still required a separation of properties in mixed marriages. The agreement could be made before, during, or after the marriage. Third, marriage institutions could conduct legal smuggling to obtain land rights in Indonesia through borrowing names (nominees), usually carried out in an unregistered marriage.